Semantic and Pragmatic Features of Hadrami Jokes (International Journal of Scientific Research and Management (IJSRM), 2022)
Humour with its different forms is a universal phenomenon. The joke is among these forms. Although they are not famous for their sense of humour, Hadrami people have their own special cultural heritage of jokes. This study attempts to investigate the semantic and pragmatic features of the punchline of a selected number of Hadrami jokes depending on two parameters of the General Theory of Verbal Humour (GTVH) which are Script Opposition (SO) and Language (LA). The linguistic constructs of LA are adopted from Leech’s (1981) associative meanings and Grice’s (1975) conversational implicature theory. The sample has been collected from the Internet and Hadrami people. After excluding the irrelevant ones, 37 jokes has been studied within the theoretical framework of this study following the discourse analysis approach of linguistic qualitative researches. The findings show that the most frequent SO in Hadrami jokes are: expected/ unexpected, and stingy/ not stingy. Also, the semantic features exceed the pragmatic ones. Within the semantic features, the connotations exceed – in their turn- the social and the collocative meanings. The focus of the pragmatic features is violating the maxims mainly under the SO parameter stingy/ not stingy. These findings prove that the punchlines of Hadrami jokes are the focal point of the joke and they represent loaded language with a great diversity of semantic and pragmatic indications.